The golden goblet - McGraw, Eloise Jarvis (New York, N.Y., U.S.A. : Puffin Books, 1986)
A young Egyptian boy struggles to reveal a hideous crime and reshape his own destiny.
"A Newbery honor book"--P. [4] of cover.
"Ages 10 up"--P. [4] of cover.
Keywords: Mystery and detective stories